PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS KEARIFAN LOKAL MATERI INDONESIAKU KAYA BUDAYA UNTUK SISWA KELAS 5 DI SEKOLAH DASAR - Mailah Mailah; Kartini Kartini; Agustinus Toding Bua (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2026)
The limited use of varied learning media has an impact on low student interest in learning, so that students are easily bored and less active in the learning process. This study aims to develop a local wisdom-based Student Worksheet on the material My Indonesia is Rich in Culture for 4th grade students in Elementary School. The research method used is Research and Development with a model consisting of five stages, namely Analysis, Design, Development, Implementation, Evaluation. The results of the feasibility validation showed a score of 86% from media experts (very feasible), 80% from material experts (very feasible), and 78% from language experts (feasible). The results of student responses to the attractiveness of the media in limited trials obtained a percentage of 82% (very feasible) and 98% from field trials (very feasible). Based on these results, the local wisdom-based Student Worksheet on the material My Indonesia is Rich in Culture is declared very feasible to be used in the learning process. This Student Worksheet is expected to be implemented more widely to support contextual learning according to the principles of the Independent Curriculum.